En Masse Retraction in Bimaxillary Protrusion and Molar Mesialization: A Case Report - Putri Intan Sitasari; Henny Susanto; Erdiarti Dyah Wahyuningtyas; I Gusti Aju Wahju Ardani (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Successful orthodontic treatment of bimaxillary protrusion requires effective anchorage control to enable anterior retraction without unwanted posterior tooth movement. Loss of molars can compromise anchorage, leading to mesial drift, space reopening, and loss of vertical control. Temporary Anchorage Devices (TADs) provide a reliable solution for achieving maximum anchorage. This case report describes the use of TADs for en masse retraction and third molar mesialization. Case: A 20-year-old female presented with a hyperdivergent profile and lip incompetence. Clinical examination revealed maxillary and mandibular incisor proclination. A gangrenous radix was present in the lower left region. Cephalometric analysis showed Class I skeletal malocclusion with a convex profile. Case Management: Based on clinical and radiographic findings, extraction therapy was planned due to arch length discrepancy. Anchorage was compromised following extraction of the lower left molar. TADs were placed to provide maximum anchorage, allowing en masse retraction of anterior teeth and controlled mesialization of the third molar. This approach minimized unwanted tooth movement and maintained vertical control throughout treatment. Conclusion: The use of TADs enabled effective anchorage control, facilitating precise en masse retraction and third molar mesialization, resulting in improved facial profile and occlusal outcomes.